The Impact of the Educational Background on the Bristolian Accent: A Case Study - Ramírez Castellanos, Felipe (Journal of Artistic Creation and Literary Research, 2025)
This paper sets out to discuss the subject matter of the impact of the educational background on the Bristolian accent, this is, to present a case study. To this purpose, ten natives from the city of Bristol have been selected in order to determine to what extent they show dialectal features in unconscious speech. In particular, the study intends to shed light on the following questions: (1) What meaningful characteristics of the Bristolian dialect are kept in unconscious speech and (2) what is Bristolian educated people’s identity towards their native dialect? In order to do so, the recordings gathered from the participants have been analysed following O’Connor and Fletcher (1999:16), Ramírez (2015), (Vinny and Stoke 2014) and Langer (2011).